Башкирсько-угорська проблема (дискурс джерел та стереотипи історіографії) - Пилипчук, Я. (Український історичний збірник, 2015)
Це дослідження присвячено найбільш актуальним питанням башкирсько-мадьярської проблеми. Велика Угорщина не тотожна Башкирії. З башкирських
етнонімів ледь два-три є спільними з угорцями. Угорський компонент брав
участь у етногенезі башкир, проте до власне угорців вони мали опосередковане
відношення. Башгірди та баджгурд східних джерел це угорці. Cвідчення ал-Масуді про баджгурдів та нукарда відносяться до угорців та болгарам. This study is dedicated to the most pressing questions of The Bashkir-Magyar
problem. Ungaria Maior is not identical Bashkiria. Only two of Bashkir ethnonyms are
connected to the Proto-Hungarians. Ugric component participated in the ethnogenesis
of the Bashkirs, but to actually Hungarians they had little to do. Bashgird (badjgurd)
of eastern sources is Hungarians. Information of al-Masoudi about of Bagjurd and
Nukarda was information about Hungarians and Bulgarians.